AMAP Progress Report to SAO meeting Anchorage, October 2015. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Programme (AMAP), 2015)
Arctic Council working group Arctic Monitoring and Assessment Programme (AMAP)s progress report. Submitted to the Arctic Council's Senior Arctic Officials meeting in Anchorage, USA, October 21-22 2015.